Pengaruh Kepemimpinan Transformasional Terhadap Kepuasan Kerja Karyawan - Akmal, Muhamad; Danupranata, Gita (Jurnal Manajemen Bisnis, 2015)
This research aims to identify and analyze the effect to of transformational leadership which consists of four dimensions:  idealized influence, inspirational motivation, individualizedconsideration and intellectual stimulation effect to job satisfaction of imployees at PT Madubaru PG PS Madukismo of Yogyakarta. The sampling technique is determined by Perposive sampling which distributing questionnaires to 78 non managerial employees at supervisor divvy. Descriptive analysis is used as the method the consists of multiple linier regression analysis, partial significan testing (Uji-t), simultaneous significant testing (Uji-f), and coeficient of determination (R2) is also used in this reserch.The result of this research swows that idealized influence, inspirational motivation, individualized consideration and intellectual stimulation which are the dimensions of transformational leadership have a significant and positive impact on satisfaction of imployees at PT Madubaru PG PS Madukismo of Yogyakarta.KeywordS: